2019
DOI: 10.1007/s13595-019-0899-7
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of bark and tension wood and role of the G-layer lignification in the gravitropic movements of 21 tropical tree species

Abstract: & Key message Gravitropic movements in angiosperm woody stems are achieved through the action of bark and/or wood motor, depending on the bark and wood fibre anatomy (with trellis structure or not; with G-layers or not). Bark motor is as efficient as wood motor to recover from tilting in young trees of 21 tropical species. & Context Angiosperm trees produce tension wood to control their orientation through changes in stem curvature. Tension wood is classified into 3 anatomical groups: with unlignified G-layer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our frequent observations of extraxylary G‐fibers complement recent findings that extraxylary tissues play important roles in movements that were previously attributed solely to xylem. For example, experiments on artificially inclined trees demonstrated that bark also influences plant posture (Ghislain et al ., 2019a,b), and Lehnebach et al . (2020) showed that phloem G‐fibers arranged in a trellis network produce higher tensile stress than species with a phloem trellis network of ordinary fibers do.…”
Section: Testing the Relationship Between Liana Climbing Mechanisms A...mentioning
confidence: 91%
“…Our frequent observations of extraxylary G‐fibers complement recent findings that extraxylary tissues play important roles in movements that were previously attributed solely to xylem. For example, experiments on artificially inclined trees demonstrated that bark also influences plant posture (Ghislain et al ., 2019a,b), and Lehnebach et al . (2020) showed that phloem G‐fibers arranged in a trellis network produce higher tensile stress than species with a phloem trellis network of ordinary fibers do.…”
Section: Testing the Relationship Between Liana Climbing Mechanisms A...mentioning
confidence: 91%
“…2J). (1-5)-α-L-arabinan pectin side chains were not labeled in G-fibers (LM6; The G-layer is often cited as being mostly cellulosic and devoid of lignin, however recent reports indicate that lignification is more widespread than previously expected (Roussel and Clair, 2015;Ghislain and Clair, 2017;Ghislain et al, 2019). By double staining sections with safranin and astra blue (Bukatsch, 1972) we typically found that the G-layer was blue (unlignified), whereas the outer S-layers generally stained red (lignified) (Fig…”
Section: Inmentioning
confidence: 99%
“…• Change-generating tissue: This consists of a single layer of cells located between the bark and wood, which causes an increase in thickness [17]. A new growth ring is added annually to the trunk of the tree, and the number of rings indicates the age of the tree.…”
Section: Quality Of Woodmentioning
confidence: 99%